Style and Influence: Computing Hebrews and the Early Christian Stylistic Fingerprint - Erich Benjamin Pracht; Thomas McCauley (Religions)
Using Hebrews as a test case, we investigate how an author’s participation in his literary network influences his writing habits. Our theoretical framework is that no author writes in a vacuum: all authors recycle stylistic habits from their literary contemporaries. We develop and implement a statistical procedure to trace stylistic influences, both in terms of which texts in an author’s literary network are influential and also in terms of which text-features are suggestive of influence. Stylistic units of analysis in this study are two-word sequences (N-Grams), 40 of which recur in Hebrews as a function of influence from the author’s literary network. We find that the author of Hebrews shares stylistic micro-patterns particularly with his co-religionists, which indicates that, already in New Testament times, the literature of emerging Christianity was developing a distinctive stylistic fingerprint, the features of which were transferred from one author to another.